2018
DOI: 10.1097/md.0000000000012190
|View full text |Cite
|
Sign up to set email alerts
|

National incidence of traumatic spinal fractures in China

Abstract: To provide a basis for disease prevention, this article aimed to clarify the incidence and risk factors of traumatic fractures in China.The China National Fracture Study (CNFS) was a retrospective epidemiological study that recruited a nationally representative sample from 8 provinces, 24 urban cities, and 24 rural counties in China using stratified random sampling and the probability proportional to size method. A total of 512,187 individuals were involved in CNFS. Incidence rates for traumatic spinal fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The Magerl AO spinal fracture classi cation system contains a comprehensive description of the fracture anatomy and uses successive grades in a hierarchical system to represent increased fracture severity [15]. According to epidemiological studies, the morbidity of type A1 and A3 fractures is the highest and that of type C fractures is the lowest [16], which is also consistent with the distribution of fracture types in our study. As the severity of the fracture increases, the form of intervertebral disc injury can also manifest as intervertebral disc edema, intradisc hemorrhage, the nucleus pulposus protruding into the vertebral body, or even a complete tear.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The Magerl AO spinal fracture classi cation system contains a comprehensive description of the fracture anatomy and uses successive grades in a hierarchical system to represent increased fracture severity [15]. According to epidemiological studies, the morbidity of type A1 and A3 fractures is the highest and that of type C fractures is the lowest [16], which is also consistent with the distribution of fracture types in our study. As the severity of the fracture increases, the form of intervertebral disc injury can also manifest as intervertebral disc edema, intradisc hemorrhage, the nucleus pulposus protruding into the vertebral body, or even a complete tear.…”
Section: Discussionsupporting
confidence: 87%
“…Williams et al found that Schmorl nodes were closely related to lumbar disc degeneration and low back pain, although these nodes were not independent predictors of low back pain [24]. In an epidemiological study of lumbar endplate injury, it was found that endplate irregularities were closely related to severe disc degeneration, and their risk ratio (RR) was as high as 16.09 for P rrmann grade IV or V degeneration [25].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent epidemiological survey, the incidence of spinal fractures is approximately 32.8/100 000, and thoracolumbar fractures account for 90% of spinal fractures. More than 50% of thoracolumbar fractures occur between T 11 –L 2 , which is stress concentration T 11 ‐L 2 ( ) .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. 19 showed that the risk of traumatic spinal fracture was 80% higher in those who did than did not consume alcohol. Similarly, Liu et al.…”
Section: Discussionmentioning
confidence: 99%